Clinical studies investigating the use of leuprorelin in Asian women with endometriosis: a review. (3rd April 2019) - Osuga, Yutaka; Torng, Pao-Ling; Jeng, Cherng-Jye
Abstract: We aimed to examine how leuprorelin has been studied for the treatment of women with endometriosis in Asia. We conducted a literature search of PubMed, the Cochrane Library and ClinicalTrials.gov. This review includes randomised trials of women with endometriosis treated with leuprorelin in Asia. Phase I–IV clinical trials published between January 1 2000 and December 31 2016 and written in English were included. Four studies were identified, showing that leuprorelin significantly improves pain and quality of life. The oestrone and oestradiol levels are decreased by leuprorelin but can be increased using an 'add-back' therapy with conjugated equine oestrogen and methoxyprogesterone. Menopause is more common in women treated with leuprorelin. The bone mineral density is reduced in women treated with leuprorelin. There are limited studies investigating the use of leuprorelin for the treatment of endometriosis in Asian populations. However, the research that has been conducted supports the use of leuprorelin in an Asian population.